Deaf Cultural Socialization: Exploring the Role of Parents in Deaf Cultural Identity Development - (:unkn) unknown (My University, 2019)
There is an assumption in the Deaf identity literature that suggests that parents’ hearing status determines the cultural identity and well-being of deaf and hard of hearing individuals. This dissertation challenges that assumption. It does so by proffering an alternative explanation of the role that parents play by introducing two forms of socialization as mechanisms through which parents influence their child’s cultural identity development and well-being. Deaf cultural socialization is the process by which parents transmit messages to children regarding the importance and meaning of Deaf culture and membership in the Deaf community. Minority status socialization is the process by which parents transmit messages to children regarding how to be successful as a deaf person in a Hearing world. Using social identity theory as a foundation and ethnic-racial socialization and identity research as a framework, this dissertation explores whether the associations between socialization and outcomes found in the ethnic-racial literature generalize to the Deaf culture. To explore this, 305 deaf and hard of hearing emerging adults from the United States completed an online survey consisting of two new measures of socialization (developed for this study), and measures of cultural identity, self-esteem, satisfaction with life, and depression/anxiety. Hearing and deaf parents engaged in socialization equally. Both Deaf cultural socialization and minority status socialization were strong predictors of cultural identity, self-esteem, and satisfaction with life, while controlling for parents’ hearing status, relationship with parents, and relevant demographic characteristics. Socialization did not predict depression/anxiety. Parents’ hearing status only predicted self-esteem. Therefore, the assumption in the literature overestimates the influence of parents’ hearing status while it underestimates the role of parents as agents of socialization in shaping cultural identity and well-being outcomes. Hearing parents, like transracially adoptive parents, promote identity development of an unshared culture through their socialization practices. More research is needed to address the gap in the literature by continuing to apply developmental theories, models, and measures to Deaf identity. Doing so will develop a more nuanced understanding of the Deaf cultural community and allow professionals to tailor services to support hearing parents as they raise a culturally different child.
Keywords: Acculturation; Culture; Deaf; Identity; Socialization; well-being